Sexual violence: The sacred witness of the Church - Pierre, Elizabeth O. (Review and expositor, 2018)
The trauma of sexual violence is pandemic. Such trauma contributes to numerous physical and psychological symptoms that affect individuals throughout their lifespan. Survivors are most inclined to turn to their faith and their religious community for support. Given the prevalence of sexual violence and the severity of its symptoms, it is critical that the Church serve as a sacred witness to facilitate the recovery process.